Modern soil microbiology (CRC Press/Taylor & Francis, 2007)
In the ten years since the publication of Modern Soil Microbiology, the study of soil microbiology has significantly changed, both in the understanding of the diversity and function of soil microbial communities and in research methods. Ideal for students in a variety of disciplines, this second edition provides a cutting-edge examination of a fascinating discipline that encompasses ecology, physiology, genetics, molecular biology, and biotechnology, and makes use of biochemical and biophysical approaches. The chapters cover topics ranging from the fundamental to the applied and describe the use of advanced methods that have provided a great thrust to the discipline of soil microbiology